2018
DOI: 10.3889/oamjms.2018.063
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of the ATP - Binding Cassette Transporter A1 (ABCA1) Rs2230806 Genetic Variation with Lipid Profile and Coronary Artery Disease Risk in an Iranian Population

Abstract: BACKGROUND:ATP - binding cassette transporter A1 (ABCA1) plays essential roles in the biogenesis of high -density lipoprotein - cholesterol. Variations in the ABCA1 gene may influence the risk of coronary artery disease (CAD).AIM:Present study aimed to investigate the association of rs2230806 (R219K) polymorphism of ABCA1 gene with the development and severity of CAD in an Iranian population.MATERIALS AND METHODS:Our study population consisted of 100 patients with angiographically confirmed CAD and 100 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
(52 reference statements)
0
19
0
2
Order By: Relevance
“…A rs2230806 genetic variation was signi cantly related to the development and severity of coronary artery disease (CAD) in an Iranian population. Moreover, the K allele of ABCA1 R219K polymorphism has been shown to exert a protective effect against CAD risk and is correlated with decreased severity of CAD, independently of plasma lipid levels [69,70]. Here, we detected a g.18167532 T/C mutation of ABCA1.…”
Section: Relevance Of Gene Variants and Tail Fat Deposition Of Sheepmentioning
confidence: 59%
“…A rs2230806 genetic variation was signi cantly related to the development and severity of coronary artery disease (CAD) in an Iranian population. Moreover, the K allele of ABCA1 R219K polymorphism has been shown to exert a protective effect against CAD risk and is correlated with decreased severity of CAD, independently of plasma lipid levels [69,70]. Here, we detected a g.18167532 T/C mutation of ABCA1.…”
Section: Relevance Of Gene Variants and Tail Fat Deposition Of Sheepmentioning
confidence: 59%
“…Literature review of these 13 variants gives contradictory results about their functional significance. One study has found significant association of the variant rs2230806 in the ABCA1 gene with susceptibility to CHD [59], whereas other studies establish this variant to have a protective role against CHD risk [60,61]. There are no supportive literature data of the role of rs2271570 in the C4orf33 gene as a CHD risk factor.…”
Section: Prioritization Of Variants Called In the Young Healthy Indivmentioning
confidence: 99%
“…Until the present, about 97 mutations have been found in the ABCA1 gene, and a large number of them are linked with Tangier disease (TD), which is described as the accretion of cholesterol in reticuloendothelial cells that increases the risk of coronary heart disease [ 17 , 18 , 19 ]. In addition to Tangier disease [ 20 , 21 ], variations and alterations in the ABCA1 gene enhance the risk of allelic disorders, such as atherosclerosis [ 22 , 23 ], ischemic stroke [ 23 , 24 ], coronary heart disease [ 25 ], type II diabetes [ 26 , 27 , 28 ], myocardial infarction (MI) [ 6 ], familial hypercholesterolaemia (FH) [ 29 ], cancer [ 30 , 31 , 32 ], Alzheimer’s disease [ 33 ], and macular degeneration [ 34 ]. Mutations in the ABCA1 gene also increase the incidence of systemic and plaque inflammation [ 35 ].…”
Section: Introductionmentioning
confidence: 99%